Special Type of Finger Replantation Techniques and Cases - Lin, Jian (Springer Singapore, 2018)
This book discusses the management of serious finger damage, which can have lifelong consequences for patients without timely and effective replantation treatment to restore the function of the hand. Featuring more than 30 cases and over 420 clinical surgical photographs, it combines systematic with thematic approaches, basic theory with clinical practice, and images with text descriptions. The book is divided into nine main sections: overview of the development history of replantation of severed fingers; anatomy of the hand; common equipment and materials; commonly used drugs; the choice of anesthesia; routine replantation methods, etc. In addition, it includes typical images for 13 special types of amputated finger replantation, and introduces readers to the replantation concept, surgical approach, surgical technique, key points of operation and matters requiring attention for each type. As such, the book offers an invaluable reference guide for finger replantation and related surgeries.